THE ROLE OF DEVIANT BEHAVIOR IN MEDIATING THE EFFECT OF ORGANIZATIONAL CULTURE AND ETHICAL CLIMATE TOWARD BANKING EMPLOYEES PERFORMANCE - Noermijati, Noermijati; Firdaus, Ema Zahra; Azzuhri, Misbahuddin (Jurnal Aplikasi Manajemen, 2021)
The objectives of this study were to analyze the mediating role of deviant behavior on the influence of organizational culture and ethical climate on employee performance. This study was conducted on 112 government-owned bank employees in Manado, using Partial Least Square (PLS) analysis. This study indicates that organizational culture and ethical climate have a significant positive effect on employee performance. Organizational culture and ethical climate also have a significant negative effect on deviant behavior. However, behavior does not have a significant effect on employee performance. Deviant behavior also does not mediate the influence of organizational culture and ethical climate on employee performance. This study places deviant behavior as a mediating variable on organizational culture and ethical climate on employee performance. An important finding from this study is that behavior does not play a role in improving employee performance, nor does it play a mediator between organizational culture or ethical climate to employee performance.